ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON RETAIL EMPLOYEES - Dinda, Benedicta; Palupiningdyah, Palupiningdyah (Management Analysis Journal, 2020)
The purpose of this study was to determine the direct and indirect influence POS and extraversion personality to OCB and affective commitment as mediation. The population in this research that all employees Aneka Jaya Supermarket Sambiroto number of 126 employees. Mechanical sampling using saturated sample so that the entire population of the research sample. Methods of data collection using a questionnaire with a Likert scale of 1-5. Data analysis method is test instrument (validity and reliability), a descriptive analysis of the respondents, and test hypotheses and test path analysis with the data processing program SPSS version 25. The results showed that all hypothesis is accepted. Therefore, the POS has positive and significant effect on affective commitment. Extraversion personality has positive and significant effect on affective commitment. Affective commitment has positive and significant effect on OCB. POS has positive and significant impact on OCB. Extraversion personality has positive and significant effect on OCB. The test results of path analysis also showed that the POS and extraversion personality and sgnifkan positive effect on OCB through affective commitment. POS positive and significant impact on OCB. Extraversion personality positive and significant impact on OCB. The test results of path analysis also showed that the POS and extraversion personality and sgnifkan positive effect on OCB through affective commitment. POS positive and significant impact on OCB. Extraversion personality positive and significant impact on OCB. The test results of path analysis also showed that POS and extraversion personality and sgnifkan positive effect on OCB through affective commitment.